JN.1: The new COVID-19 variant of concern? - Ruby Dhar; Hiya Aidasani; Om Saswat Sahoo; Arun Kumar; Subhradip Karmakar (Asian Journal of Medical Sciences, 2024)
Emergence of new variants of COVID-19 is nothing new. Different variants evolved with additional mutations of the virus as part of the viral replication cycle have different infectious properties. JN.1 is the latest COVID-19 variant that seems to circulate the globe contributing to many infections and hospitalizations labeling it a variant of interest by the WHO. The scientific community has yet to understand its full lethal potential if any. In this mini-review, we summarized the facts known so far about this variant and its possible consequences if any for humanity.